HUBUNGAN ANTARA ASUPAN ZAT BESI, ASAM FOLAT DAN VITAMIN C DENGAN KADAR HEMOGLOBIN PADA REMAJA PUTRI USIA 15-18 TAHUN DI SMK BINA NUSANTARA UNGARAN BARAT KABUPATEN SEMARANG - Nurwahidah; Mulyasari, Indri; Pontang, Galeh Septiar (JURNAL GIZI DAN KESEHATAN, 2018)
Background :Femaleadolescents aged 10-19 years who experience anemia increase by 68.24%. Lack of iron intake, folic acid and vitamin C is a factor of theoccurrence of anemia in female adolescents. Objective :to determine the correlationbetween intake of iron, folic acid and vitamin C with hemoglobin level infemale adolescents aged15-18 years at SMK Bina Nusantara, West Ungaran Semarang Regency Methods :This study was acorrelationalcorrelative study using cross-sectionalapproach at SMK Bina Nusantara. Samples were 70 students taken by Proportional Random Samplingmethod. Iron intake, folic acid intake and vitamin C intake were measured by semiquantitative FFQ. Hemoglobin was measured by using hemoglobinometer. Data analysis used Spearman Rank correlation test and Person product moment (Î± = 0,05). Result : iron intake was included as category severe deficiency 54.3%, mild deficiency 2.9%, moderate deficiency2.9%, normal 32% and excessive intake 7.1%. Folic acid intake was included as category severe deficiency 54,3%, mild deficiency 17,1%, moderate deficiency 8,6%, normal 18,6%, and excessive intake 5,7%. vitamin intake was included as category severe deficiency 25.7%, mild deficiency 2.9%, moderate deficiency 5.7%, normal 12.9%, and excessive intake 52.9%. For the levels of hemoglobin, most of them experiencedanemia as many as 52,9% (37 respondents) and not anemia as many as 47,1% (33 respondents). There was a correlation between iron intake and folic acid intake with hemoglobin level (p = 0.0001; p = 0.0003), there was no correlation between vitamin C and hemoglobin level (p = 0,304). Conclusion :There is a correlation between iron intake and folic acid intake with hemoglobin levels. There is no association between vitamin C and hemoglobin levelsKeywords: iron, folic acid, vitamin C, hemoglobin level Abstrak : Latar Belakang : Remaja putri umur 10-19 tahun yang mengalami anemia mengalami peningkatan sebesar 68,24%. Kurangnya asupan zat besi, asam folat dan vitamin C merupakan salah satu faktor terjadinya anemia pada remaja putri. Tujuan : Untuk mengetahui hubungan antara asupan zat besi, asam folat dan vitamin cdengan kadar hemoglobin pada remaja putri usia 15-18 tahun di SMK Bina Nusantara Ungaran Barat Kabupaten Semarang. Metode : Jenis penelitian studi kolerasi dengan pendekatan cross sectional di SMK Bina Nusantara . Sampel 70 siswa diambil dengan metode Proportional Random Sampling. Asupan zat besi, asupan asam folat dan asupan vitamin C menggunakan FFQ semikuantitatif. Hemoglobin diukur menggunakan Hemoglobinometer. Analisis data menggunakan uji kolerasi Spearman Rank dan Person product moment (Î± = 0,05). Hasil : Asupan zat besi kategori defisit berat 54,3%, defisit ringan 2,9%, defisit sedang 2,9%, normal 32% dan diatas kebutuhan 7,1%. Asupan asam folat kategori defisit berat 54,3%,defisit ringan 17,1 %, defisit sedang 8,6% normal 18,6%, dan diatas kebutuhan 5,7%. Asupan vitamin C kategori defisit berat 25,7%, defisit ringan 2,9%, defisit sedang 5,7%, normal 12,9%, dan di atas kebutuhan 52,9 %, dan Kadar hemoglobin yang termassuk anemia 52,9% (37) dan tidak anemia 47,1% (33). Ada hubungan antara asupan zat besi dan asupan asam folat dengan kadar hemoglobin (p=0,0001 ; p=0,0003), tidak ada hubungan antara vitamin C dengan kadar hemoglobin (p=0,304). Simpulan : Ada hubungan antara asupan zat besi dan asupan asam folat dengan kadar hemoglobin. Tidak ada hubungan antara vitamin C dengan kadar hemoglobin